Business confidence in South Africa: Identifying key domestic drivers and the nature of their inpact. - Maredza, Andrew; Nyamazunzu, Zvikomborero (My University, 2016)
The primary objective of this paper is to empirically assess the magnitude, direction and significance of the impact of selected domestic macroeconomic fundamentals on business confidence index for the South African economy. This particular focus of the paper comes at a time in the history of the South African economy when the business climate and investor confidence is at its lowest. According to South African Chamber of Commerce and Industry (SACCI, 2016), the business confidence index reached a 22-year low record of 79.6 in December 2015 before slipping further down to its all-time low of 79.3 in May this year. The auto-regressive distributive lag (ARDL) model proposed by Pesaran et al (2001) is employed on quarterly data spanning the period 1975 – 2015 and 2002 – 2015 for two models; total business confidence and financial services business confidence respectively. We attempt to explore the relationship between business confidence and selected domestic macroeconomic indicators. Empirical results showed that real economic growth, interest rate, exchange rate, inflation outlook and stock market performance have significant impacts on business confidence. Hence, our study empirically supports the notion that macroeconomic stability drives business confidence. The results stress the need by the government to ensure that the business environment is conducive for doing business in order to boost business confidence. By instilling and preserving the needed business confidence in the financial sector and the larger economy, growth prospects and aspirations of a country improve.
Keywords: Business confidence; Bounds testing; Investor perception; Investor confidence; ARDL model; Economic recession